2002
DOI: 10.1094/cchem.2002.79.2.257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactic Acid on Protein Solubilization and Starch Yield in Corn Wet‐Mill Steeping: A Study of Hybrid Effects

Abstract: Cereal Chem. 79(2):257-260To better understand the role of lactic acid (LA) in corn wet-milling, steeping studies were performed on different yellow dent corn hybrids using four different solutions containing LA, sulfur dioxide (SO 2 ), a combination of LA and SO 2 , or no added chemicals. Although there was variation in protein solubilization among the hybrids, protein release was consistently higher when LA was included in the steepwater than when it was excluded (both with and without SO 2 ) . . Several gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…According to Shandera, Packhurst, and Jackson (1995), lactic acid increased the rate of sulfur dioxide when it was added to the steeping solution. For that grain, Dailey (2002) has determined that such increase was due to protein solubilization present in corn grain with the consequent benefit on starch recovery. As we are interested in developing a wet-milling procedure for amaranth grain, future research will be directed towards establishing a correlation between water absorption increase, protein solubilization and starch recovery using SO 2 solutions with and without addition of lactic acid.…”
Section: So 2 and Lactic Acidmentioning
confidence: 99%
“…According to Shandera, Packhurst, and Jackson (1995), lactic acid increased the rate of sulfur dioxide when it was added to the steeping solution. For that grain, Dailey (2002) has determined that such increase was due to protein solubilization present in corn grain with the consequent benefit on starch recovery. As we are interested in developing a wet-milling procedure for amaranth grain, future research will be directed towards establishing a correlation between water absorption increase, protein solubilization and starch recovery using SO 2 solutions with and without addition of lactic acid.…”
Section: So 2 and Lactic Acidmentioning
confidence: 99%
“…The reduction of soakwater when compared with the conventional steepwater is due to the reduced soaking time and the solubilizing effects of the reducing agent (SO 2 ) and lactic acid (Dailey 2002). Dotted line represents average conventional corn wet-milling yield for germ using standard, highly reproducible, laboratory procedure.…”
Section: Figmentioning
confidence: 99%
“…Wang et al (2000) found no significant differences in sorghum starch yield when grains were steeped with 0.2 or 0.3% SO 2 and lactic acid. Dailey (2002) suggested that, at increasing lactic acid concentrations, more protein from the endosperm matrix is solubilized and higher amounts of starch are recovered. Addition of increasing amounts of CWDE significantly increased starch yields in both types of grains.…”
Section: Wet-millingmentioning
confidence: 99%